2016
DOI: 10.1016/j.epsl.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17 anomaly in soil nitrate: A new precipitation proxy for desert landscapes

Abstract: The nitrogen cycle in desert soil ecosystems is particularly sensitive to changes in precipitation, even of relatively small magnitude and short duration, because it is already under water stress. This suggests that desert soils may have preserved past evidence of small variations in continental precipitation. We have measured nitrate (NO 3-) concentrations in soils from the Atacama (Chile), Kumtag (China), Mojave (US), and Thar (India) deserts, and stable nitrogen and oxygen isotope (15 N, 17 O, and 18 O) abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, nitrate in desert soils may possess nonzero Δ 17 O values due to limited nitrification in desert ecosystems. The soil nitrate Δ 17 O values are negatively correlated with mean annual precipitation in desert landscapes (Wang et al, 2016). We noted that the mean annual precipitation (1979–2015) at the Western TP, one of major dust sources over the TP (Li et al, 2012), ranged from ~70 to ~180 mm (http://en.tpedatabase.cn/portal/index.jsp).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nitrate in desert soils may possess nonzero Δ 17 O values due to limited nitrification in desert ecosystems. The soil nitrate Δ 17 O values are negatively correlated with mean annual precipitation in desert landscapes (Wang et al, 2016). We noted that the mean annual precipitation (1979–2015) at the Western TP, one of major dust sources over the TP (Li et al, 2012), ranged from ~70 to ~180 mm (http://en.tpedatabase.cn/portal/index.jsp).…”
Section: Resultsmentioning
confidence: 99%
“…We noted that the mean annual precipitation (1979–2015) at the Western TP, one of major dust sources over the TP (Li et al, 2012), ranged from ~70 to ~180 mm (http://en.tpedatabase.cn/portal/index.jsp). Although soil nitrate isotopic compositions over the TP were not determined, soil nitrate Δ 17 O values over the Western TP might be as high as ~15‰ based on the empirical estimation by Wang et al (2016). The potential role of soil nitrate in altering atmospheric nitrate Δ 17 O values should be further investigated by direct isotopic analysis of soil nitrate from the TP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential mechanism for large quantities of nitrate to be transported into soils is millennial-scale atmospheric deposition, followed by partial biologic processing. A recent study showed that nitrogen cycling in soils depends on mean annual precipitation (MAP) with Δ 17 O values that are increasingly shifted away from the atmospheric value with increasing MAP due to increased biological nitrogen cycling. Wang et al developed an empirical equation to describe this shift: …”
Section: Results and Discussionmentioning
confidence: 99%
“…A recent study showed that nitrogen cycling in soils depends on mean annual precipitation (MAP) with Δ 17 O values that are increasingly shifted away from the atmospheric value with increasing MAP due to increased biological nitrogen cycling. Wang et al developed an empirical equation to describe this shift: …”
Section: Results and Discussionmentioning
confidence: 99%